Is there a universal allometric scaling of metabolism? Cephalopods as a case study - Lopes, Vanessa Madeira, 1989- (2013)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2012